Associações entre perfis de orientação de valor social e práticas de gestão de capital de giro - Rotta, Clayton José (2020)
This research focused on the relationships between the individual's social value orientation profile and the decision-making of this employee regarding a request to expand the supplier average payment period, which is in financial difficulties, and how this request would directly influence the supplier’s financial management. The working capital management in companies is a widely studied theme, and this research brought a social variable, where the decision-making has a directly impact, and the individual who conducts the negotiation has the social value orientation which do not entirely matches with the company’s directives. Regarding the social value orientation, individual difference measure, the individual is classified in: pro-social, the person that maximizes the team work and who cares about the measure, the individual is classified in: pro-social, the person that maximizes the team work and who cares about the other; individualists, who maximize their self-interest; and, competitors, who maximize the relative advantage between themselves and the other. One hundred and fourteen undergraduate students from different courses and semesters were interviewed in this academic experiment, to set the type of social value orientation and confront it with the decision-making of requesting an expansion in the supplier average payment period, in order to verify whether the social value orientation takes part in the decision-making or not. As a result, the study, through measuring the rates differences, could not validate the research hypotheses. The results should be observed considering the study limitations, which considered the undergraduate student’s perception, many of them young and with little professional experience, and other variables that may influence the relationships analyzed